2019
DOI: 10.1177/1461444819894304
|View full text |Cite
|
Sign up to set email alerts
|

Digital touch for remote personal communication: An emergent sociotechnical imaginary

Abstract: This article makes legible emergent social imaginaries of digital touch for remote communication in personal relationships, with attention to digital touch interfaces. It draws on data from rapid prototyping research workshops with apprentice professionals embedded within digital communication. Touch is discussed with respect to four analytical themes: materiality, body, emplacement and temporality. We illustrate how participants’ past and present experiences and future visions of remote digital touch thread t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 40 publications
(53 reference statements)
0
18
0
1
Order By: Relevance
“…Additional characteristics found to be important were synchronicity and symmetry. When looking at the data, the participants indicated that the message having a shared meaning was important corresponding to findings of Jewitt et al (2019). According to the participants' responses, this is something that can be more easily achieved with devices that operate symmetrically (i.e., with the same input and output).…”
Section: Discussionmentioning
confidence: 93%
“…Additional characteristics found to be important were synchronicity and symmetry. When looking at the data, the participants indicated that the message having a shared meaning was important corresponding to findings of Jewitt et al (2019). According to the participants' responses, this is something that can be more easily achieved with devices that operate symmetrically (i.e., with the same input and output).…”
Section: Discussionmentioning
confidence: 93%
“…Historically and theoretically we have learned much about smell (e.g., Classen et al, 1994) and touch (e.g., Paterson, 2007). More recently, several innovative research teams (e.g., Jewitt et al, 2021;Verbeek and van Campen, 2013), are opening up smell and touch research with exciting multimodal experiments, pushing for more odorous and more tactile scholarship, including in teaching, documentation, and dissemination.…”
Section: Introduction To a Textural Methodsmentioning
confidence: 99%
“…In recent years, the concept of sociotechnical imaginaries gained intellectual traction, giving rise to several studies dedicated to the examination of technology-based innovations across countries and political regimes: energy production and remote sensing in the United States (Lawrence, 2020; Smith and Tidwell, 2016), smart cities and multinational corporations (Sadowski and Bendor, 2019) as well as digital touch and bioenergy (Jewitt et al, 2021; Levidow and Raman, 2020) in the United Kingdom, Internet in Russia (Keidiia, 2019), autonomous driving in Germany (Graf and Sonnberger, 2020), family farming in Argentina (Goulet, 2020) and food security in Sweden (Eriksson et al, 2020), just to mention some of the most recent endeavours.…”
Section: Theoretical Frameworkmentioning
confidence: 99%